The impact of drinking on smoking cessation outcomes among Hong Kong Chinese youth smokers - Ka Yan Ho; Katherine Ka Wai Lam; Qi Liu; Ting Mao; Funa Yang; Mulualem Getaneh Belay; Cynthia Sau Ting Wu; Mak Yim Wah (Scientific Reports)
Drinking is a common unhealthy behaviour among youth smokers aged 25 or below. However, the effects of drinking on smoking cessation outcomes are not well understood. This study aimed to explore the impact of drinking on smoking cessation outcomes among Hong Kong Chinese youth smokers who received smoking cessation counselling. This study adopted a cross-sectional design at the Youth Quitline, which is the only government-funded hotline providing telephone smoking cessation counselling to Hong Kong smokers aged 25 or younger. Of the 142 participants at the six-month follow-up, 75 were in the drinking group and 67 in the non-drinking group. Multiple logistic regression analyses were performed to identify any significant differences in self-reported quit rates, smoking reduction by at least 50%, quit attempts, and biochemically validated quit rates between the drinking and non-drinking groups. The results showed a significant difference in self-reported quit rate between the two groups at 6-month, but no significant difference in smoking reduction by at least 50%, quit attempts, and biochemically validated quit rate. Alcohol drinking and male were identified as significant factors decreasing self-reported quit rate at 6 months. The study revealed that drinking could decrease quit rates among young smokers who received counselling, but not their smoking reduction or quit attempts. Given the negative impact of drinking on smoking abstinence and the increased popularity of drinking among the youth, assessment of alcohol use and brief advice on smoking are recommended to be an integral part of smoking cessation counselling for youth smokers.